“Cenas Cariocas, 2ª suíte” para clarineta e piano de Guerra Vicente: um estudo interpretativo - Vieira, Taís Vilar (2014)
This work has as its object of study the piece "Cenas Cariocas, 2ª Suíte" for Bb clarinet and piano. José Guerra Vicente (1906-1976), a Portuguese composer that became a Brazilian citizen, wrote this piece in 1964, during his nationalist phase. The main objective of this research is to offer an interpretive discussion of the work, focusing on the clarinet part. Historical, structural and technical aspects are addressed. The methodology has included a literature review, an analysis of the work, interviews and questionnaires. As a result, information that may bring contributions to the construction of interpretations of the version for clarinet and piano work are presented.